(untitled) (Indian Journal of Animal Production and Management, 2024)
Yak has been very closely associated with the culture, religion, and social fabric of the pastoral people in Ladakh. A study was carried out to document the feeding practices involved in rearing of yak and its bovine crosses in Ladakh. Results indicate that availability of fodder was seasonal with the fodder being available only between the months of April to October and had to be stored for harsh winters. Common property resources (CPRs) were found to be the primary and only fodder source and all the yak rearers were feeding a mixed feed including green, dry and home-grown concentrate depending on the availability. Usually, the animals were allowed to graze in the pastures (CPRs) for most of the time and were stall-fed with collected and stored grasses only during extremely harsh winters. During stall-feeding, animals were fed once a day and it was usually a group feeding of different animal species all together. Yak rearers in general lacked the knowledge regarding feed improvement and feeding of mineral mixture but were aware about feeding of salt to animals.